Pemanfaatan Tongkol Jagung Sebagai Bahan Deodoran Alami untuk Mengurangi Bau dan Bakteri pada Sepatu - Yescenia Sigiro; Siska L Batu; Eki Monalisa Br; Yohanna Sitanggang; Putri Kemala Dewi Lubis (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Bad odor and bacterial growth in shoes are common issues experienced by many users, primarily due to the damp conditions after use. Widely available synthetic chemical-based shoe deodorants often raise health concerns and have a negative impact on the environment. Furthermore, corncobs, an abundant agricultural waste product, are underutilized, despite their carbon content and porous structure that have the potential to absorb odors and inhibit bacterial growth. This study aims to test the effectiveness of processed corncobs as a natural deodorant in reducing odor and bacteria in shoes. The research method used a qualitative approach through literature review and interviews with several informants to obtain data on community needs and the potential use of corncobs. The results indicate that corncobs have significant ability to absorb odors and reduce moisture, thereby suppressing the growth of odor-causing bacteria in shoes. Furthermore, the use of corncobs as a natural deodorant is considered safer, environmentally friendly, and has economic prospects due to its readily available and low-cost raw materials.